Phytorestoration of abandoned mining and oil drilling sites - Bauddh, Kuldeep; Korstad, John; Sharma, Pallavi (College teacher of Life Sciences) (Elsevier, 2021)
Phytorestoration of Abandoned Mining and Oil Drilling Sites presents case studies and the latest research on the most effective methods to address the large amounts of waste materials released due to mining and oil drilling. In particular, phytoremediation is described as a novel, eco-friendly, cost-effective method for extracting toxic compounds by plants for the restoration of contaminated sites. Plantings on these contaminated areas lead to the removal of toxic substances such as heavy metals and hydrocarbons, improvement in the physicochemical and biological properties of the soil, long-term forest ecosystem rehabilitation, restoration of ecosystem productivity, stability and biological diversity, and reductions in CO2. Utilizing worldwide examples, this book discusses the potential of phytoremediation as an ideal solution for sites contaminated by mining and oil drilling sites.